Review Perhitungan Biaya Wheeling - Yusuf Susilo Wijoyo; Sasongko Pramono Hadi; Sarjiya (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
Wheeling is a solution to the complexity of transmission network constructing problem. With the wheeling concept, a power plant owner can deliver electricity to its load without having to construct a transmission network. The owner of the power plant can utilize the transmission network belonging to other entities. The wheeling concept is an interesting thing in terms of increasing current renewable energy penetration. This is due to the construction of the transmission network, which is one of the obstacles in increasing renewable energy penetration. Fairness of wheeling costs is still one important topic. The discussion regarding wheeling costs emphasizes that the costs charged to each party involved can meet the fairness principle, which is in accordance with their respective contributions to the implementation of wheeling. Broadly speaking, research related to wheeling can be grouped into research for developing wheeling cost calculation methods and research for developing wheeling cost allocation methods. The development of the wheeling cost calculation method also includes the development of cost components that can be included in the cost calculation. This study summarizes the discussion of wheeling costs on three aspects, namely calculation methods, cost components, and cost allocation mechanisms.